64.1k views
8 votes
CosA/1-sinA=1+sinA/cosA​

User SharkCop
by
5.4k points

1 Answer

5 votes

Answer:

see explanation

Explanation:

Using the trigonometric identity

sin²x + cos²x = 1 ⇒ cos²x = 1 - sin²x

Consider the left side


(cosA)/(1-sinA) ← multiply numerator/denominator by (1 + sinA)

=
(cosA(1+sinA))/((1-sinA)(1+sinA)) ← expand denominator using FOIL

=
(cosA(1+sinA))/(1-sin^2A)

=
(cosA(1+sinA))/(cos^2A) ← cancel cosA on numerator/ denominator

=
(1+sinA)/(cosA)

= right side , thus proven

User Willurd
by
5.1k points